Laboratorij na čipu - Mežnaršič, Tadej (Matrika, 2014)
In this paper I present lab-on-a-chip technology, starting with short history overview of the subject. Then I limit the discussion to droplet based microfluidics, focusing on in depth explanation of physical phenomena on which the technology is based, e.g. surface tension, viscosity, dielectrophoresis, Marangoni effect etc. I conclude the paper with examples of useful applications of droplet based microfluidics in material science and research of biomolecular processes, cells and elastic properties of fibres.
Keywords: droplets; fluid mechanics; kapljična mikrofluidika; mehanika tekočin; microfluidics